2022
DOI: 10.1039/d1tc05176h
|View full text |Cite
|
Sign up to set email alerts
|

Laser-patterned carbon coatings on flexible and optically transparent plastic substrates for advanced biomedical sensing and implant applications

Abstract: Plasma and laser-based processing for tailoring DLC thin film properties for state-of-the-art wearable sensing applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Resonant wavelengths are generated by manipulating the electromagnetic fields associated with the light emitted from photonic crystals. As such, an electromagnetic standing wave showing intensities relative to the intensities of an illuminating light source is generated [ 45 , 46 , 47 ]. Furthermore, it has been demonstrated that gold nanoparticles (AuNP) with localized surface plasmon resonance (LSPR) overlap with the resonant electromagnetic field of a photonic crystal, resulting in a significant amplification of the absorption efficiency [ 48 ].…”
Section: Microscopic Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Resonant wavelengths are generated by manipulating the electromagnetic fields associated with the light emitted from photonic crystals. As such, an electromagnetic standing wave showing intensities relative to the intensities of an illuminating light source is generated [ 45 , 46 , 47 ]. Furthermore, it has been demonstrated that gold nanoparticles (AuNP) with localized surface plasmon resonance (LSPR) overlap with the resonant electromagnetic field of a photonic crystal, resulting in a significant amplification of the absorption efficiency [ 48 ].…”
Section: Microscopic Techniquesmentioning
confidence: 99%
“…Chen et al studied the use of a label‐free, submicron resolution approach called photonic crystal enhanced microscopy, which utilizes photonic crystal biosensor surface as a substrate for cell attachment, to understand the attachment and morphology of murine dental stem cells. The time lapse study involving chemotaxis with a chemoattractant is shown in Figure 4 [ 46 ]. Zhao et al studied the use of a photonic crystal optical biosensor coated with a recombinant spike protein for the quantitative detection of serological human IgG levels against the SARS‐CoV‐2 virus.…”
Section: Microscopic Techniquesmentioning
confidence: 99%
“…The chemical routes make use of highly toxic and hazardous chemicals; unwanted chemical impurities may adversely affect the catalytic properties. 3 Reduction of GO with a laser is referred to as a "green route" as it is environmentally safe. Studies comparing the properties of GO reduction using femtosecond, nanosecond (ns), and continuous-wave lasers have shown that rGO obtained with ns laser pulses exhibits superior properties.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal route for reduction of GO is not commercially viable as the conventional furnace-based thermal reduction of GO exposes the whole substrate to high temperatures, leading to electrode degradation. The chemical routes make use of highly toxic and hazardous chemicals; unwanted chemical impurities may adversely affect the catalytic properties …”
Section: Introductionmentioning
confidence: 99%
“…Innovations in growing customized 2D h-BN and its nanoflakes for specific applications are in high demand for the development of next-generation integrated devices [ 16 ]. These limitations have prompted research into nonequilibrium ways to fabricate 2D materials at near-ambient temperatures [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%